Promoting Careers in Neurology: Mentorship of Medical Students - Zuzuarregui, José-Rafael; Wu, Connie; Hohler, Anna DePold (Seminars in Neurology, 2018)
Research in neurological disorders is expanding at a phenomenal pace, and the need for neurologists is increasing as the population ages. This results in a critical requirement for medical students entering the neurology pipeline. Mentoring, whether formal or informal, ensures that students are inspired and supported to enter the field of neurology. Students should also receive structured mentoring throughout their longitudinal curriculum. Informal mentoring programs enable expanded opportunities for collaborations in education, research, and outreach. Faculty, residents, fellow medical students, and other health professionals all participate in medical student mentoring. Each relationship offers unique aspects to individual growth and development. Specific programmatic guidance and mentoring qualities are presented in this paper.
Keywords: mentoring; medical students; medical school